EFFECTIVENESS LEARNING LAPTOPS AND HANDPHONE TO UNDERSTANDING STUDENT LEARNING - Al Karim Rambe, Rahmansyah Fadlul; Masdalena, Masdalena; Coal, Kintan Aulia; Rahmah, Lutfiah (International Journal of Cultural and Social Science, 2024)
smartphone use in supporting learning activities in circles student. With use analysis. Results study show effectiveness use smartphones in circles student support activity Study student in matter increase outlook student And Also make it easy student in Study, do task nor looking for material lesson.